1985
DOI: 10.1021/bi00343a039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of detergent polar and apolar structure upon the temperature dependence of beef heart cytochrome c oxidase activity

Abstract: The temperature dependence of lipid-depleted beef heart cytochrome c oxidase activity was studied in a series of chemically homogeneous detergents. The detergents that were tested included C10 to C18 maltosides, C8 to C12 glucosides, C8 to C16 Zwittergents, and C12 poly(oxyethylene) ethers. The observed rates of electron transport were dependent upon the structure of the polar head group and the length of the hydrocarbon tail. Of the detergents tested, the alkyl maltosides were the best in terms of both high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 28 publications
4
28
0
Order By: Relevance
“…Our suggestion concerning the respective role of the alkyl chain and the polar head group in the perturbation by DM of ATPase is strengthened by data obtained on another membrane protein, cytochrome c oxidase. Alkyl maltosides of different chain lengths were shown to modify cytochrome c oxidase activity in a manner similar to that of synthetic phospholipids of comparable chain lengths (Robinson et al, 1985). In addition, chemical labeling of cytochrome c oxidase also suggested that the maltose head group of DM interacted with the protein more strongly than the alkyl ether headgroup of Triton X-100, chemically similar to that of C,,E, (Estey et al, 1990).…”
Section: Molecular Basis Of Dm Perturbationmentioning
confidence: 85%
See 1 more Smart Citation
“…Our suggestion concerning the respective role of the alkyl chain and the polar head group in the perturbation by DM of ATPase is strengthened by data obtained on another membrane protein, cytochrome c oxidase. Alkyl maltosides of different chain lengths were shown to modify cytochrome c oxidase activity in a manner similar to that of synthetic phospholipids of comparable chain lengths (Robinson et al, 1985). In addition, chemical labeling of cytochrome c oxidase also suggested that the maltose head group of DM interacted with the protein more strongly than the alkyl ether headgroup of Triton X-100, chemically similar to that of C,,E, (Estey et al, 1990).…”
Section: Molecular Basis Of Dm Perturbationmentioning
confidence: 85%
“…For instance, extensive comparative studies showed DM to be superior to all other detergents tested for the purification and the maintenance of the native structure of soluble cytochrome c oxidase (e.g. Rosevear et al, 1980;Robinson et al, 1985). It has also been used for the purification of a photosystem I1 core complex from spinach (Bricker et al, 1985) and from algae (de Vitry et al…”
mentioning
confidence: 99%
“…COX was isolated from bovine heart essentially as described in [22] (a modified Fowler‐type preparation) according to a protocol kindly provided by Dr. A. Musatov (Department of Biochemistry, UTHSC, San Antonio). The enzyme was reconstituted in egg lecithin vesicles by cholate dialysis method [23].…”
Section: Methodsmentioning
confidence: 99%
“…Preparation A involves sodium cholate solubilization of sodium deoxycholate treated Keilin-Hartree heart muscle particles followed by purification of CcO by ammonium sulfate precipitation as previously described [29]. The resulting purified enzyme was dissolved at ~100 µM in pH 7.4 buffer containing 25 mM sodium cholate and stored at −60 °C.…”
Section: Methodsmentioning
confidence: 99%